Deciphering structure and charge carrier behavior in reduced-dimensional perovskites - Sun, Kun; Guo, Renjun; Liu, Shangpu; Guo, Dengyang; Jiang, Xiongzhuo; Huber, Linus F.; Liang, Yuxin; Reus, Manuel A.; Li, Zerui; Guan, Tianfu; Zhou, Jungui; Schwartzkopf, Matthias; et al. (Advanced functional materials, 2024)
Reduced-dimensional perovskites (RDPs) have advanced perovskite optoelectronic devices due to their tunable energy landscape, structure, and orientation. However, the origin of structural and photophysical property changes when moving from low-dimensional to high-dimensional RDPs remains to be understood. This study systematically reveals structural and photophysical properties of slot-die-coated Dion-Jacobson (DJ) and Ruddlesden-Popper (RP) RDPs with different dimensionalities. RP RDPs with lower dimensionality (n = 2) exhibit a dominant n = 2 phase, preferential out-of-plane orientation, and longer charge carrier lifetime compared with DJ RDPs. In addition, the formation kinetics of RDPs with higher dimensionality (n = 4) are unraveled by in situ X-ray scattering, showing the favorable formation of the lower-n phase in RP RDPs. The formation of these lower-n phases is thermodynamically and stoichiometrically favored, while these phases are likely in the form of an “intermediate phase” which bridges the 3D-like and lower-n phases in DJ RDPs. DJ RDPs with higher dimensionality demonstrate comparable phase purity, preferential orientation, spatially vertical phase homogeneity, and longer charge carrier lifetime. As such, DJ-based perovskite solar cells (PSCs) (n = 4) demonstrate better photostability under operational conditions than RP-based PSCs. Thus, the work paves the way for the utilization of RDPs to upscale PSCs.